KECEMASAN MENGHADAPI KEMATIAN PADA LANJUT USIA - Ermawati Ermawati; Shanty Sudarji (Universitas Bunda Mulia, 2013)
The process of aging is a natural process of the human face. In this process, the most crucial stage is the stage of aging. In this stage, the human beings are naturally occurring decline or change in the physical, psychological and social which interact with each other. Deterioration in the elderly occurs because cells aging process that can result in organ weakness, physical deterioration, the onset of various diseases, especially degenerative diseases. Eldery is also seen as a time of biological degeneration accompanied by suffering with various diseases period and the awareness that everyone will die, the death anxiety would be an important psychological problems in the elderly. This study uses a qualitative design with the case study method. Qualitative studies as a process trying to get a better understanding of complexity in human interaction. Case study method allowed the researchers to gain a complete understanding of the interrelationships and integrated many facts and dimensions of the particular case to be studied. Keywords: elderly, death anxiety